PENGARUH LITERASI KEUANGAN DAN KUALITAS PELAYANAN TERHADAP PENGAMBILAN KEPUTUSAN MENGGUNAKAN JASA LAYANAN BANK SYARIAH YANG DIMEDIASI OLEH RELIGIUSITAS - Puteri Nabila; Ridwan Nurdin (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2023)
This study aims to analyze the effect of financial literacy and service quality on decision making using Islamic banking services mediated by religiosity. This study uses a quantitative approach with a sample of 100 respondents who are active undergraduate students at Syiah Kuala University. Data obtained by distributing questionnaires to respondents. The data analysis technique used is Path Analysis and Sobel Test. The results of the research analysis showed that financial literacy and service quality had a positive and significant effect on religiosity. Financial literacy, service quality and religiosity have a positive and significant effect on decision making. The results of the Sobel test on the indirect effect show that financial literacy does not have a positive and significant effect on decision making with religiosity as a mediating variable. Service quality has a positive and significant influence on decision making with religiosity as a mediating variable. It is hoped that every Islamic Bank institution can improve the quality of its services so that this bank becomes one of the student targets in making decisions about using Islamic Bank services.